Analysis of Time Control Strategies Using The Critical Path Method (CPM) In The Development of The Java Residence Cluster For Mass-Product - Budi Prasetiya, Kukuh; Patriadi, Andi; Sajiyo, Sajiyo (Green Publisher Indonesia, 2025)
The increasing complexity and scale of industrial and construction projects demand efficient management techniques to ensure timely delivery, cost-effectiveness, and adherence to quality standards. This study focuses on the implementation of the Critical Path Method (CPM) in managing the construction of the Cluster Java Residence in Sidoarjo to enhance time efficiency. The research investigates the effectiveness of CPM in identifying and mitigating delays by analyzing project activities, their interdependencies, and schedule flexibility using forward and backward pass calculations. Secondary data from project schedules and primary data from field observations were analyzed to identify critical paths and optimize project timelines. Results indicate that the implementation of product quality control in the construction of housing units in the Java Residence Cluster is still under control, although the average number of defects or complaints per housing unit is relatively high. The issues of defects or complaints in the construction of housing units in the Java Residence Cluster are caused by factors related to humans, machines or tools, materials, and work methods.